(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2024)
Jürgen Fuchs (1950-1999) was one of those GDR-born writers, whose biographies were not only shaped by the SED regime, but which also successfully deformed it. He was one of the few individuals who eloquently and unwaveringly exposed the taboos and mechanism of the totalitarian state. Fuchs’s literary oeuvre is a testimony of his times as well as a confrontation with the communist regime and its legacy in the form of the Stasi records. Coloured autobiographically and saturated with his own life experience, his writing takes the reader on a shocking journey into the time of the second German dictatorship, allowing them a look behind the scenes of the (post) socialist society. At the same time it brings about a realisation that as an intellectual Fuchs felt obliged to interfere whenever it was necessary to prevent violence, lies and forgetting about the past. This article traces the literary development of Fuchs as an independent writer and examines his motivation not to remain silent, to strive for truth and justice, and to provoke debate, whenever necessary.